Topical nitric oxide releasing nanoparticles are effective in a murine model of dermal Trichophyton rubrum dermatophytosis - Mordorski, Breanne; Costa-Orlandi, Caroline Barcelos [UNESP]; Baltazar, Ludmila M.; Carreño, Leandro J.; Landriscina, Angelo; Rosen, Jamie; Navati, Mahantesh; Mendes-Giannini, Maria Jose Soares [UNESP]; Friedman, Joel M.; Nosanchuk, Joshua D.; Friedman, Adam J. (Elsevier, 2017)
Systemic therapies are preferred for treating dermal dermatophytosis due to inadequate penetration of topical agents. However, systemic antifungals are associated with off-target effects and limited tissue penetration, and antimicrobial resistance is a growing concern. To address this, we investigated topical nitric oxide-releasing nanoparticles (NO-np), which have been used against superficial fungal infections and bacterial abscesses. In addition to enhanced penetration and permeation conferred by nanoparticles, nitric oxide, a broad-spectrum multi-mechanistic antimicrobial agent, offers decreased likelihood of resistance development. In the current study, NO-np inhibited Trichophyton rubrum in vitro, as well as in a murine model of dermal dermatophytosis. In mice, NO-np reduced fungal burden after three days, with complete clearance after seven. Furthermore, NO-np decreased tissue IL-2, 6, 10 and TNFα, indicating earlier attenuation of the host inflammatory response and decreased tissue morbidity. Thus, topical NO-np represent an attractive alternative to systemic therapy against dermal T. rubrum infection.